2016
DOI: 10.3390/polym8040077
|View full text |Cite
|
Sign up to set email alerts
|

Static and Dynamic Properties of Semi-Crystalline Polyethylene

Abstract: Properties of extruded polymers are strongly affected by molecular structure. For two different semi-crystalline polymers, low-density polyethylene (LDPE) and ultra-high molecular weight polyethylene (UHMWPE), this investigation measures the elastic modulus, plastic flow stress and strain-rate dependence of yield stress. Also, it examines the effect of molecular structure on post-necking tensile fracture. The static and dynamic material tests reveal that extruded UHMWPE has a somewhat larger yield stress and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 29 publications
(38 reference statements)
2
30
0
Order By: Relevance
“…It was shown that tensile properties were significantly dependent on the orientation of molecular structure originating from different morphologies developed during the polymer deformation process [ 6 ]. Anisotropy effect in tensile properties was also investigated through tension tests in 0°, 45°, and 90° relative to extrusion direction for two grades of polyethylene (LDPE and UHMWPE) [ 18 ]. No significant difference on tensile properties was observed among samples and it was concluded that the extruded polyethylene material is isotropic in terms of tensile behavior [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that tensile properties were significantly dependent on the orientation of molecular structure originating from different morphologies developed during the polymer deformation process [ 6 ]. Anisotropy effect in tensile properties was also investigated through tension tests in 0°, 45°, and 90° relative to extrusion direction for two grades of polyethylene (LDPE and UHMWPE) [ 18 ]. No significant difference on tensile properties was observed among samples and it was concluded that the extruded polyethylene material is isotropic in terms of tensile behavior [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anisotropy effect in tensile properties was also investigated through tension tests in 0°, 45°, and 90° relative to extrusion direction for two grades of polyethylene (LDPE and UHMWPE) [ 18 ]. No significant difference on tensile properties was observed among samples and it was concluded that the extruded polyethylene material is isotropic in terms of tensile behavior [ 18 ]. However, Grommes et al [ 19 ] reported significant anisotropy effect in elastic modulus for blow molded HDPE between extrusion direction and blowing direction (perpendicular to extrusion) for blow molded HDPE.…”
Section: Introductionmentioning
confidence: 99%
“…Figure shows the typical stress–strain curves of semicrystalline thermoplastics. These curves have four characteristic behaviors: elastic, initial necking, cold drawing (plastic) regions, and fracture point . As shown in Figure (a), adding a higher concentration of PP to LDPE increased both the tensile strength, which is a measure of a material to withstand a tensile force and toughness property, which is the ability to absorb energy and undergo extensive plastic deformation without rupturing.…”
Section: Resultsmentioning
confidence: 97%
“…However, the elastic-plastic constitutive model considering both strain rate effect and temperature effect was not studied in Ref. [8][9][10][11][12][13][14][15][16][17][18]. On this basis, the research considering the strain rate effect and temperature effect was carried out in the present paper.…”
Section: Introductionmentioning
confidence: 99%